Integrated water resource management in the Segura Hydrographic Basin: An artificial intelligence approach - Otamendi, Urtzi; Maiza, Mikel; Olaizola, Igor G.; Sierra, Basilio; Florez, Markel; Quartulli, Marco (Journal of environmental management, 2024)
Managing resources effectively in uncertain demand, variable availability, and complex governance policies is a significant challenge. This paper presents a paradigmatic framework for addressing these issues in water management scenarios by integrating advanced physical modelling, remote sensing techniques, and Artificial Intelligence algorithms. The proposed approach accurately predicts water availability, estimates demand, and optimizes resource allocation on both short- and long-term basis, combining a comprehensive hydrological model, agronomic crop models for precise demand estimation, and Mixed-Integer Linear Programming for efficient resource distribution. In the study case of the Segura Hydrographic Basin, the approach successfully allocated approximately 642 million cubic meters (hm3) of water over six months, minimizing the deficit to 9.7% of the total estimated demand. The methodology demonstrated significant environmental benefits, reducing CO2 emissions while optimizing resource distribution. This robust solution supports informed decision-making processes, ensuring sustainable water management across diverse contexts. The generalizability of this approach allows its adaptation to other basins, contributing to improved governance and policy implementation on a broader scale. Ultimately, the methodology has been validated and integrated into the operational water management practices in the Segura Hydrographic Basin in Spain. •Framework for Integrated Water Resource Management based on advanced technologies.•Weather forecasting & advanced physical simulation to predict resource availability.•Agronomic Modelling using remote sensing imagery to estimate irrigation demand.•Optimal resource management for demand–supply, ecological and economic perspective.•Operational integration of the decision-making system into a fullscale infrastructure.